Delayed Graduation and University Dropout: A Review of Theoretical Approaches - Carmen Aina; Eliana Baici; Giorgia Casalone; Francesco Pastore (Institute of Labor Economics (IZA), 2019)
This paper surveys the theoretical approaches used in the literature to study the phenomenon of delayed graduation and university dropout. The classical human capital model does not contemplate failure, which the amended human capital model does. Delayed graduation and university dropout are two stages of the same decision repeated over the years to step aside or leave when the net returns to education expected ex ante are negative. Failure can also be taken as a signal of the real skills of individuals who do not succeed to gain a higher level of education. The job search approach underlines the role of positive/negative local labor market conditions as a factor able to explain choices of investment in human capital. Within the bargaining approach, the decision to delay graduation or dropout from university is related to bargaining within the family between parents and children: the former give their children better consumption opportunities in return for their presence at home. Although the amended human capital model is certainly the most compelling one, the other approaches help framing factors which are neglected in the human capital model, forming a well-structured body of knowledge to better understand the phenomenon under scrutiny, while also suggesting a set of policy tools to better control it.
Keywords: H52; H75; I21; I23; I28; J13; J24; 330; elapsed time to degree; postsecondary education; ex post and ex ante returns to education; university fees; human capital; signaling; job search; bargaining